The immunomodulatory activity of extracellular vesicles derived from endometrial mesenchymal stem cells on CD4+ T cells is partially mediated by TGFbeta. (19th August 2018) - Álvarez, Verónica; Sánchez‐Margallo, Francisco Miguel; Macías‐García, Beatriz; Gómez‐Serrano, María; Jorge, Inmaculada; Vázquez, Jesús; Blázquez, Rebeca; Casado, Javier G.
Abstract: Endometrial mesenchymal stem cells (endMSCs) reside in the basal and functional layer of human endometrium and participate in tissue remodelling, which is required for maintaining the regenerative capacity of the endometrium. The endMSCs are multipotent stem cells and exhibit immunomodulatory effects. This paper aimed to evaluate the regulatory effects of extracellular vesicles derived from endMSCs (EV‐endMSCs) in the setting of T cell activation. In vitro stimulations of lymphocytes were performed in the presence of EV‐endMSCs. These in vitro ‐stimulated lymphocytes were functionally and phenotypically characterized to distinguish CD4+ and CD8+ T cell differentiation subsets. Moreover, the inhibition of TGFβ was performed with neutralizing antibodies. The phenotype and nanoparticle tracking analysis of the EV‐endMSCs demonstrated that they are similar in terms of size distribution to other mesenchymal stem cells‐derived exosomes. The in vitro assays showed an immunomodulatory potential of these vesicles to counteract the differentiation of CD4+ T cells. The quantification of active TGFβ in EV‐endMSCs was found to be very high when compared with extracellular vesicles‐free concentrated supernatants. Finally, the neutralization of TGFβ significantly attenuated the immunomodulatory activity of EV‐endMSCs. In summary, this is the first report demonstrating that EV‐endMSCs exhibit a potent inhibitory effect against CD4+ T cell activation, which is partially mediated by TGFβ signalling.